Antioxidant, Total Phenolic and Flavonoid Content of Selected Nigerian Medicinal Plants - Agbo, Matthias Onyebuchi; Uzor, Philip Felix; Akazie Nneji, Uchenna Nneamaka; Eze Odurukwe, Chidozie Uzoma; Ogbatue, Uchenna Basilia; Mbaoji, Emmanuel Chukwunwike (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Plant phenolics and flavonoids play a great role in scavenging free radicals in the body and act as antioxidants. Thus their determination is sometimes nedded. Total antioxidant capacity, total phenolic and flavonoid contents of the extracts of 10 medicinal plants (Lochnera rosea, Allamanda cathartica, Asplenium platyneuron, Euphorbia prostrate, Baphia nitida, Crotolaria retusa, Zapoteca portoricensis, Platycerium bifurcatum, Mussaenda afzelii and Craterosiphon scandens) from 7 botanical families growing in the tropical rainforest of Nigeria were included in this study. The total antioxidant capacity of the extracts was assessed by using the phosphomolybdate method. The phenolic content was determined by using Folin-Ciocalteau assay, while the total flavonoid was determined by the aluminium chloride colorimetric assay. The results obtained showed that the total antioxidant capacity for all the extracts were in the range of 0.888 ± 0.75 to 0.938 ± 0.00 mg EAA/g. The results showed that E. prostrate, P. bifurcatum and A. platyneuron were found to be the richest source of phenolic (97.77 ± 0.77, 87.62 ± 1.22 and 82.33 ± 0.30 mg GAE/g) while B. nitida and M. afzelii had the least total phenolic content (11.67 ± 0.09 and11.18 ± 0.30 mg GAE/g). The highest total flavonoid content was revealed in P. bifurcatum (648.67 ± 12.3 mg QE) while M. afzelii also had the least total flavonoid content (3.67 ± 0.00 mg QE/g). The ratio of flavonoid to the phenolic in each extract was also determined to ascertain extracts that are rich in flavonoids. Dhaka Univ. J. Pharm. Sci. 14(1): 35-41, 2015 (June)